Dampak Nilai Tukar (Kurs) terhadap Neraca Pembayaran di Indonesia: Pendekatan Autoregressive Distributed Lag. - Syafitri, Aidillia; Sentosa, Sri Ulfa; Artha, Dwirani Puspa (Jurnal Kajian Ekonomi dan Pembangunan, 2025)
The purpose of this study is to determine how the exchange rate (Kurs) affects the balance of payments in Indonesia. This study uses time series data from 1993-2023. The analysis technique used is Autoregressive Distributed Lag (ARDL). Based on the ARDL test, the exchange rate has a positive relationship and a significant effect on the balance of payments in the short term, while in the long term the exchange rate has a positive relationship but has no significant effect on the balance of payments. National income and interest rates have a negative relationship and have a significant effect on the balance of payments in the short term, while in the long term national income and interest rates have no significant effect but have a negative relationship on the balance of payments.